PENOLAKAN DAN PEMBATALAN ASY-SYAFI’I RA TOTAL TERHADAP ISTIHSAN SEBAGAI DALIL HUKUM - Adrianto, Adrianto; Haslinda, Haslinda; Sitorus, Khalid (Al-Usroh : Jurnal Hukum Keluarga Islam, 2025)
Background. The total rejection and cancellation of ash-Shafi'i RA against Istihsan as a legal postulate, both Istihsan carried out by Imam Abu Hanifah RA and his disciples and Istihsan carried out by his followers, and Istihsan carried out by Imam Malik RA and his disciples and followers. Purpose. The study examines the rejection and cancellation of asy-Shafi'i RA against Istihsan. Method. This literature study illustrates the rejection and cancellation of asy-Shafi'i RA against Istihsan. Data was collected from various main sources in the form of books and opinions. The data were analyzed descriptive-qualitatively in the form of causal relationships, associative relationships, and comparisons. Result. The rejection and cancellation of ash-Shafi'i RA against Istihsan is the Istihsan of Imam Abu Hanifah which is narrated by his disciples according to Imam ash-Shafi'i RA has caused many legal decisions that are considered strange because they have left the meaning of the Qur'an and sunnah. As for the accusations of Hanafiah scholars regarding istihsan carried out by as-Shafi'i in a number of his ijtihad practices, none of them have been proven to be true. Which means that Imam as-Shafi'i was consistent in his rejection of Istihsan in his ijtihad.